“A Framework for Identifying the sources of Local currency Price stability with an empirical application” (2007): A Research Report - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
A research report on Goldberg, Pinelopi K., and Hellerstein, Rebecca (2007). "A framework for identifying the sources of local currency price stability with an empirical application," Staff Reports 287, Federal Reserve Bank of New York.
Keywords: A1; 330; law of one price